Development of STEM-Based Environmental Change Module to Enhance Environmental Literacy - Saragih, Putri Prisillia; Tanjung, Indayana Febriani (Biosfer: Jurnal Tadris Biologi, 2023)
At this time there are many learning modules circulating both printed and electronic (online), however, the development of STEM-based modules that have been carried out does not see the effectiveness of the module. The purpose of this research is to see the validity, practicality and effectiveness of the module. The 4D research methodology (Define, Design, Development, Disseminate) was used. This research was conducted in class X Senior High School. The results showed that the Material Validity Test research obtained 98.57% (Very Valid), the Media Expert Validation Test assessment was 98.6% (Very Valid), the response assessment by the biology teacher was 85% (Practical), the average student response assessment was 86.07% (Practical). The STEM-based environmental change module produced from the research conducted is valid, practical, and effective in increasing the level of environmental literacy among grade X students at Senior High School.ABSTRAK: Pada saat sekarang ini modul pembelajaran sudah banyak beredar baik ditemukan secara cetak maupun juga elektronik (online), walaupun demikian pengembangan modul berbasis STEM yang sudah dilakukan tidak melihat keefektifan dari modul. Tujuan dari penelitian ini adalah untuk melihat validitas, kepraktisan, dan keefektifan modul. Metodologi penelitian 4D (Define, Design, Development, Disseminate) digunakan. Penelitian ini dilakukan pada kelas X SMAS. Hasil penelitian menunjukkan bahwa penelitian Uji Validitas Materi yang diperoleh 98,57% (Sangat Valid), penilaian Uji Validasi Ahli Media adalah 98,6% (Sangat Valid), penilaian respon oleh guru biologi adalah 85% (Praktis), rata-rata penilaian respon siswa adalah 86,07% (Praktis). Modul perubahan lingkungan berbasis STEM yang dihasilkan dari penelitian yang dilakukan adalah valid, praktis, dan efektif dalam meningkatkan tingkat literasi lingkungan di kalangan siswa kelas X di SMAS.